Improving Students' Linguistic Skills at English Classes (In the Field of Tourism) (Journal of Pedagogical Inventions and Practices, 2022)
English Language has played an important role in the development of tourism and in this field, English is used widely for travel as well as in client contact and is of outmost interest at the tertiary level. English for tourism is one of the most attractive areas of English for Specific Purposes (ESP) because, after all, all of us are tourists on various occasions nowadays